Intrinsically Stabilized Plastic Optical Fiber Link Subject to External Optical Feedback - Azusa Inoue; Yasuhiro Koike (IEEE Photonics Journal, 2019)
We develop a graded-index plastic optical fiber (GI POF) that can significantly stabilize a multimode fiber (MMF) link with a vertical-cavity surface-emitting laser (VCSEL) subject to external optical feedback. It is demonstrated that the dominant mechanism for this stabilization effect is the strong mode coupling of the GI POF, which is closely related to the polymer-specific microscopic heterogeneities in the GI POF core material. Such mode coupling decreases correlation between the problematic reflected light field and VCSEL cavity field, increasing tolerance of the MMF link for external optical feedback. Our developed GI POF with specific microscopic heterogeneities prevents the external-optical-feedback-induced critical destabilization observed for silica GI MMFs. These results suggest that the stabilization effect can be controlled by microscopic properties regardless of the fiber attenuations and core refractive indices.